Benzothiazolium salts as reagents for the deoxygenative perfluoroalkylthiolation of alcohols - Ariamajd, Armin; Gerwien, Nils J.; Schwabe, Benjamin; Dix, Stefan; Hopkinson, Matthew N. (Beilstein Journal of Organic Chemistry, 2021)
A series of 2-(perfluoroalkylthio)benzothiazolium (BT-SRF) salts have been synthesized that serve as convenient sources of hitherto underexplored perfluoroalkylthiolate anions. An investigation of their reactivity in a deoxygenative nucleophilic substitution reaction led to the development of an unprecedented process that provides pentafluoroethyl and heptafluoropropyl thioethers directly from readily available alcohols.
Keywords: alcohols; benzothiazolium salts; deoxygenative reactions; fluorine; perfluoroalkylthiolation; thioethers

(untitled) - Müller, K.; Faeh, C.; Diederich, F. (Science, 2007)

(untitled) - Purser, S.; Moore, P. R.; Swallow, S.; Gouverneur, V. (Chem. Soc. Rev., 2008)

(untitled) - Wang, J.; Sánchez-Roselló, M.; Aceña, J. L.; del Pozo, C.; Sorochinsky, A. E.; Fustero, S.; Soloshonok, V. A.; Liu, H. (Chem. Rev., 2014)

(untitled) - Gillis, E. P.; Eastman, K. J.; Hill, M. D.; Donnelly, D. J.; Meanwell, N. A. (J. Med. Chem., 2015)

(untitled) - Fujiwara, T.; O’Hagan, D. (J. Fluorine Chem., 2014)

(untitled) - Berger, R.; Resnati, G.; Metrangolo, P.; Weber, E.; Hulliger, J. (Chem. Soc. Rev., 2011)

(untitled) - Xu, X.-H.; Matsuzaki, K.; Shibata, N. (Chem. Rev., 2015)

(untitled) - Barata-Vallejo, S.; Bonesi, S.; Postigo, A. (Org. Biomol. Chem., 2016)

(untitled) - Xiong, H.-Y.; Pannecoucke, X.; Besset, T. (Chem. – Eur. J., 2016)

(untitled) - Pannecoucke, X.; Besset, T. (Org. Biomol. Chem., 2019)

(untitled) - Mampuys, P.; McElroy, C. R.; Clark, J. H.; Orru, R. V. A.; Maes, B. U. W. (Adv. Synth. Catal., 2020)

(untitled) - Xiao, X.; Zheng, Z.-T.; Li, T.; Zheng, J.-L.; Tao, T.; Chen, L.-M.; Gu, J.-Y.; Yao, X.; Lin, J.-H.; Xiao, J.-C. (Synthesis, 2020)

(untitled) - Hein, M.; Miethchen, R.; Schwäbisch, D. (J. Fluorine Chem., 1999)

(untitled) - Miethchen, R.; Hein, M. (Carbohydr. Res., 2000)

(untitled) - Boiko, V. N. (Beilstein J. Org. Chem., 2010)

(untitled) - Yagupolskii, L. M.; Maletina, I. I.; Petko, K. I.; Fedyuk, D. V.; Handrock, R.; Shavaran, S. S.; Klebanov, B. M.; Herzig, S. (J. Fluorine Chem., 2001)

(untitled) - Andrzejewska, M.; Yépez-Mulia, L.; Cedillo-Rivera, R.; Tapia, A.; Vilpo, L.; Vilpo, J.; Kazimierczuk, Z. (Eur. J. Med. Chem., 2002)

(untitled) - Johansson, A.; Poliakov, A.; Åkerblom, E.; Wiklund, K.; Lindeberg, G.; Winiwarter, S.; Danielson, U. H.; Samuelsson, B.; Hallberg, A. (Bioorg. Med. Chem., 2003)

(untitled) - Lishchynskyi, A.; Grushin, V. V. (J. Am. Chem. Soc., 2013)

(untitled) - Umemoto, T.; Kuriu, Y. (Chem. Lett., 1982)

(untitled) - Wakselman, C.; Tordeux, M. (J. Org. Chem., 1985)

(untitled) - Boiko, V. N.; Shchupak, G. M. (J. Fluorine Chem., 1994)

(untitled) - Roques, N. (J. Fluorine Chem., 2001)

(untitled) - Exner, B.; Bayarmagnai, B.; Matheis, C.; Goossen, L. J. (J. Fluorine Chem., 2017)

(untitled) - Xiang, J.-X.; Xu, X.-H.; Qing, F.-L. (J. Fluorine Chem., 2017)

(untitled) - Luo, Z.; Yang, X.; Tsui, G. C. (Org. Lett., 2020)

(untitled) - Baert, F.; Colomb, J.; Billard, T. (Angew. Chem., Int. Ed., 2012)

(untitled) - Alazet, S.; Billard, T. (Synlett, 2015)

(untitled) - Jiang, L.; Qian, J.; Yi, W.; Lu, G.; Cai, C.; Zhang, W. (Angew. Chem., Int. Ed., 2015)

(untitled) - Xu, B.; Li, D.; Lu, L.; Wang, D.; Hu, Y.; Shen, Q. (Org. Chem. Front., 2018)

(untitled) - Matheis, C.; Bayarmagnai, B.; Jouvin, K.; Goossen, L. J. (Org. Chem. Front., 2016)

(untitled) - Haszeldine, R. N.; Kidd, J. M. (J. Chem. Soc., 1955)

(untitled) - Liu, J.-B.; Xu, X.-H.; Chen, Z.-H.; Qing, F.-L. (Angew. Chem., Int. Ed., 2015)

(untitled) - Scattolin, T.; Pu, M.; Schoenebeck, F. (Chem. – Eur. J., 2018)

(untitled) - Glenadel, Q.; Bordy, M.; Alazet, S.; Tlili, A.; Billard, T. (Asian J. Org. Chem., 2016)

(untitled) - Dix, S.; Jakob, M.; Hopkinson, M. N. (Chem. – Eur. J., 2019)

Eur. Pat. Appl. - Hopkinson, M.; Dix, S. (Fluorine-containing compounds for use as nucleophilic reagents for transferring functional groups onto high value organic compounds, 2019)
International Pat. Appl. PCT/EP2020/050031, Jan 2, 2020.

(untitled) - Tironi, M.; Maas, L. M.; Garg, A.; Dix, S.; Götze, J. P.; Hopkinson, M. N. (Org. Lett., 2020)

(untitled) - Mukaiyama, T. (Angew. Chem., Int. Ed. Engl., 1979)